Brain-wide 3D imaging of neuronal activity in Caenorhabditis elegans with sculpted light. - Schrödel, Tina; Prevedel, Robert; Aumayr, Karin; Zimmer, Manuel; Vaziri, Alipasha (Nature Methods, 2013)
Recent efforts in neuroscience research have been aimed at obtaining detailed anatomical neuronal wiring maps as well as information on how neurons in these networks engage in dynamic activities. Although the entire connectivity map of the nervous system of Caenorhabditis elegans has been known for more than 25 years, this knowledge has not been sufficient to predict all functional connections underlying behavior. To approach this goal, we developed a two-photon technique for brain-wide calcium imaging in C. elegans, using wide-field temporal focusing (WF-TeFo). Pivotal to our results was the use of a nuclear-localized, genetically encoded calcium indicator, NLS-GCaMP5K, that permits unambiguous discrimination of individual neurons within the densely packed head ganglia of C. elegans. We demonstrate near-simultaneous recording of activity of up to 70% of all head neurons. In combination with a lab-on-a-chip device for stimulus delivery, this method provides an enabling platform for establishing functional maps of neuronal networks.